Resources and energy potentials in rural Bangladesh : a case study of four villages - Quader, Abdul A.K.M. (CSC LondonGB, 1986)
Examines and evaluates existing energy resources and requirements in four villages in northern Bangladesh. Discusses population, distribution of households and homesteads, land ownership and use, agriculture, fuel use, transport, sanitation and health care, education, employment, food habits, and loans of money.